Studies on Dexmedetomidine as an Adjuvant to Levobupivacaine in Ultrasound Guided Supraclavicular Brachial Plexus Block - V. Waindeskar; K. Bhatia; S. Garg; J. Kumar; S. Songir; V. Singla (Highlights on Medicine and Medical Science Vol. 3, 2021)
Background: Alpha-2 agonists are added to local anesthetic agents to extend the duration of peripheral nerve blocks. Objective: We evaluated the effect of combining dexmedetomidine with levobupivacine with respect to duration of motor and sensory block and duration of analgesia. In our study, while the onset time of both sensory and motor blocks were shortened in the drug group, the duration of analgesia was significantly prolonged. Materials and Methods: Sixty patients of ASA grade I or II aged between 18-60 years, posted for elective upper limb surgeries were enrolled for a prospective, randomized, double-blind study. Patients were divided into two groups, the control group B and the study group BD. In group B (n = 30), 30 ml of 0.325% levobupivacaine; and in group BD (n = 30), 30 ml of 0.325% levobupivacaine + 1 µg/kg dexmedetomidine were given for ultrasound guided supraclavicular brachial plexus block. Duration of motor and sensory block and time to first rescue analgesia were recorded. Results: Demographic profile and surgical characteristics were similar in both groups. The onset times for sensory and motor blocks were significantly shorter in BD group (p < 0.05), while the duration of sensory and motor blocks and duration of analgesia (DOA) was significantly longer in BD group. Heart rate level and SBP and DBP levels in group BD were significantly lower 15-20 min after block (p< 0.05). Bradycardia was observed in two patients in the group BD. No other adverse effects were observed in either of the groups. Conclusion: Dexmedetomidine added as an adjuvant to levobupivacaine for supraclavicular brachial plexus block significantly shortens the onset time and prolongs the duration of sensory and motor blocks and duration of analgesia.